(untitled) (Journal of Universal Science Research, 2024)
As the demand for learning foreign languages is increasing at a rapid rate, many educators are forced to explore new ways of teaching foreign languages to improve the engagement of students. Due to the advancement in modern information technologies and intelligent computing system, many teachers can provide their students with new tools for their learning productivity and higher academic achievements. The particular reason for this circumstance is that these systems can help teachers to meet the diverse learning needs of language learners through using universally designed curriculum and assessment. This scientific article aims to present a conceptual framework that includes the use of digital technologies and Universal Design for Learning principles to improve the language learning process. By applying UDL principles and advanced information technologies, foreign language teachers can move away from traditional methods that only focus on teacher-centered classrooms into a more modern and effective way of teaching.